The conscientious objection of medical personnel to therapeutic abortion regulated in the Therapeutic Abortion Protocol - Pérez Dávila, Belú Fiorella (2019)
The Therapeutic Abortion Protocol (PAT), in force since 2014, regulates the procedure for the execution of therapeutic abortions nationwide. Establishes an open list of clinical entities for access, under the Informed Consent of the pregnant woman and not including the rights of her child. This rule generates in the medical professional the obligation to perform abortions, which may contradict the precepts of his conscience about the indiscriminate respect of all human life, restricting his constitutional right to freedom of conscience. In this article, we analyze the content of said freedom and the right to Conscientious Objection, as well as the coherence between the PAT and Article 119 of the Criminal Code (CP), to determine if with this rule the Objection of Awareness (OC) of the medical professional to the execution of said abortion, for colliding with his deep conviction to respect all human life, regardless of his stage of human development.